A COMPARATIVE STUDY ON BIOCHEMICAL AND PIGMENT PROFILE OF SIX RED SEAWEED SPECIES (Applied Biological Research, 2024)
This study evaluated the biochemical composition of six red seaweed species, collected from the Pamban Bridge area in Palk Strait, Tamil Nadu (India). Among the species, Acanthophora spicifera had highest carbohydrate content (48.18%) and lowest protein content (1.32%), while Halymenia dilatata had highest protein content (15.08%). Hypnea valentiae showed lowest carbohydrates (21.03%). Pigment analysis revealed that Kappaphycus alvarezii had highest concentration of chlorophyll a and lowest concentration of chlorophyll d. Notably, phycobiliproteins, a characteristic pigment in red seaweeds, were abundant in H. dilatata, especially R-phycoerythrin, while A. spicifera and H. dilatata consistently had R-phycocyanin, and H. valentiae had higher R-allophycocyanin. Moisture content in test red seaweeds ranged from80.13 to 87.12%, and dry matter from 12.88 to 19.87%. H. valentiae possessed highest total phenolic content (3.17 mg gallic acid equivalents g-1). The study depicts the potential of these test red seaweeds as source of bioactive compounds for their use in food, nutraceuticals, and pharmaceuticals.
Keywords: Biochemical compounds; phenols; pigments; red seaweeds